OUTCOME OF LAPAROSCOPIC CHOLECYSTECTOMY FOR GALL STONES DISEASE IN PATIENTS WITH LIVER CIRRHOSIS - Khan, Nasir; Siddiq, Ghulam (Journal of Ayub Medical College Abbottabad, 2013)
Background: Laparoscopic cholecystectomy (LC), a gold standard procedure for cholelithiasis, is associated with higher incidence of bile duct injuries and perioperative bleeding. These complications are of further concern when LC is carried out on patients with liver cirrhosis. Although LC is now increasingly being performed for cholelithiasis in cirrhotic patients, the safety of the procedure is debatable in this group of patients. Methods: We retrospectively analysed 82 LCs, performed between January 2002 and December 2011, in cirrhotic patients with gall stone disease for perioperative complications. Patients were sub-classified into Class A, B and C based on child-Pugh classification of severity of liver cirrhosis. Intergroup comparisons were carried out using ANOVA, and p‰¤0.05 was considered significant. Results: LC was successfully completed in all but 3 patients (3.7%). None of the cirrhotic patients had bile duct injury. Class C patients (n=27) had higher frequency of perioperative bleeding than Class B and A (p=0.03). Class C patients had comparatively longer stay (5.42 days; range 4-8 days) than Class B (3 days; range 2-6) and Class A (2.74 days; range 2-4), (p=0.01). There was no mortality in our series. Conclusion: The outcome in Child A and B cirrhosis is comparable to non-cirrhotic patients undergoing LC for gall stone disease. Conversion rate and perioperative bleeding in these groups of patients is acceptable in relevance to LC in non-cirrhotic patients. Child C patients however need careful assessment and determination of operative risk versus advantages. Keywords: Laparoscopic cholecystectomy, Cirrhosis, Cholelithiasis, Chronic liver disease